Mengoptimalkan Peran Bank Sampah melalui Pelatihan Digital Marketing - Cepi Yazirin; Margianto Margianto; Oktriza Melfazen (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Digital marketing plays a strategic role in optimizing the performance and social impact of waste bank groups. By leveraging digital technology, waste banks can expand the reach of environmental education, raise public awareness, and improve operational efficiency. Digital marketing can help waste banks build a strong brand, expand their market, and attract more community participation. The methods used in these activities include direct outreach and training. In addition, this training provides relevant skills for managing social media, websites, and e-commerce, which can ultimately increase income from recycling waste. In the long term, the integration of digital marketing will make waste banks more independent, competitive, and contribute more significantly to environmental conservation. The result of the training can drive the economic sustainability of waste banks by opening up opportunities for business collaboration and partnerships through digital platforms.